Digital influencers: um estudo sociológico sobre o empreendedorismo digital e a cultura da recomendação - Souza, Veronica Laveli de (2019)
This dissertation analyzes the digital influencers that make use of the Instagram platform in the scenario of online sociability enhancement, and the consolidation of the oligopoly business model of the Silicon Valley companies that currently concentrate the use of the Internet in its majority. In spite of the rhetoric of providing services or facilitating the sharing of experiences, these companies base their business model on the maintenance of advertising platforms where the users act as a "co-producer" and "partner" although- often – they are exploited in their creative capacity. The objective of this research is to study how Instagram users negotiate the boundaries between the public and the private, which would elevate them to the position / condition of digital influencers by their ability to influence their followers in the consumption of products, brands and services. As specific objectives, we seek to understand how the identity of digital influencers is constructed by analyzing critically the income, class, and ethnic-racial origin that are behind this construction. Finally, we investigate whether digital influencers can be understood as entrepreneurs by seeking to constitute a kind of "me-company" in a period of high unemployment rates and a decrease in labor rights which gain favor among entrepreneurs.